Policy Review: Phisical Need Minimum of Beneficiaries in Social Institution - B Mujiyadi; Nunung Unayah (Jurnal Penelitian Kesejahteraan Sosial, 2014)
On behalf of healthy life, every human being should fulfill their basic need. One among basic needs is food in order to gain energy to do daily activities, which based on sufficient nutrition standard. Every one needs at least 2.150 kilo caloryper day. Beneficiaries in Social Home Services are also need energy, so the management of those Social Home Services should have compulsary to fulfill the beneficiaries need. Meanwhile, the govermnet have decided a certain policy in terms of oil price. The decision impacted on market rate of food price. Ministry of Social Affairs as top manager of social services should reponsible to secure the beneficiaries of social home services. Hence, the Ministry should decide a new policy in terms of securing social services. It will take in to account of main indicator of social services for the beneficiaries in social institutions.